Kualitas Pelayanan Pembayaran Pajak Kendaraan Bermotor Melalu Layanan Drive Thru Pada Sistem Manunggal Satu Atap (Samsat) Katang Kabupaten Kediri - Bahari Ilmy, Ahmad Farkhan; Hertati, M.Si , Dr. Diana (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
Service is the main task of the government in providing public services both at the central and regional levels, to facilitate access to public services as stipulated in Law Number 23 of 2014 concerning Regional Government, the central government gives authority to regional governments in regulating and managing regional government affairs in certain fields in carrying out public affairs with the aim of accelerating community welfare through strategies to improve services, empowerment and community participation. One type of public service that needs to get more attention is the service in the field of paying regional taxes, Motor Vehicle Tax is a regional tax which is used as one of the largest sources of income, the East Java Provincial Revenue Agency in improving the quality of motorized vehicle tax collection services to the public is through superior services, such as: Samsat Drive Thru, Samsat Payment Point, Samsat Corner, Mobile Samsat Mandiri Mobile Samsat, Samsat Link, E-Sasat East Java, ATM Samsat East Java, Embosser Machine, and the newest service is in collaboration with PT. Indonesian post. The Kediri Regency Samsat Katang Joint Office is one of the public service places for the payment of Motor Vehicle Tax (PKB) and Motorized Vehicle Ownership Fee (BBNKB) which are under the Technical Implementation Unit of the East Java Province Revenue Agency Kediri. The SAMSAT Drive Thru service unit is one of the breakthroughs in efforts to improve service quality at the Katang Joint Samsat Office, Kediri Regency. In this study the authors used a qualitative research approach with the intention of providing a comprehensive and in-depth overview of research studies. The target of this research study used the Zeithaml, Parasuraman theory and Berry (Pasolong, 2013: 135) in knowing that there are five dimensions as a measure of consumer or customer satisfaction, namely Tangibles, Reliability, Responsiveness, Assurance, Emphaty. The results of the study show that the service on the Tangibles aspects of the service staff is of good quality, but the facilities and infrastructure aspects have not provided comfort because the place for payment is too narrow if two cashiers are applied so that the facilities and infrastructure aspects provide poor quality, then the Reliability of the service staff in the process of completing the quality service is already very good, while the Responsiveness of service personnel responds, helps provide fast and appropriate services which is very good, as well as guarantees provided by service officers such as timely completion of services, supervision and legitimacy which are appropriate and of very good quality, the empathetic aspect of service officers is polite polite and non-discriminatory service staff which shows very good quality, but in the hospitality aspect it provides not good quality.